A security improved image encryption scheme based on chaotic Baker map and hyperchaotic Lorenz system. (2016) - Fu, Chong; Wen, Zhan-kao; Zhu, Zhi-liang; Yu, Hai
In recent years, chaos-based image cipher has been widely studied and a growing number of schemes based on permutation-diffusion architecture have been proposed. However, most of the existing schemes are based on low-dimensional chaotic systems and have the drawbacks of small key space and weak security. In this paper, we present a security improved image cipher which utilises chaotic Baker map and hyperchaotic Lorenz system for permutation and diffusion. Compared with ordinary chaotic systems, hyperchaotic systems, with more complex dynamical behaviours and number of system variables, offer greater potential for secure cryptosystem construction. In diffusion stage, a plain-image related key stream generation scheme is introduced, which further improves the security against known/chosen plaintext attack. Extensive security analysis has been performed on the proposed scheme, including the most important ones like key space analysis, key sensitivity analysis, differential analysis and various statistical analyses, which has demonstrated the satisfactory security of the proposed scheme.